Comparison of Uncinate Process Cancer and Non-Uncinate Process Pancreatic Head Cancer - Liu, Chang (J Cancer, 2016)
The special anatomical position accounts for unusual clinicopathological features of uncinate process cancer. This study aimed to compare clinicopathological features of patients with uncinate process cancer to patients with non-uncinate process pancreatic head cancer. Total 160 patients with pancreatic head cancer were enrolled and classified into two groups: uncinate process cancer and non-uncinate process pancreatic head cancer. We found that the ratio of vascular invasion was significantly higher in patients with uncinate process cancer than in patients with non-uncinate process pancreatic head cancer. In addition, the rate of R1 resection was significantly higher in patients with uncinate process cancer. Furthermore, the median disease-free survival (11 months vs. 15 months, p=0.043) and overall survival (15 months vs. 19 months, p=0.036) after R0 resection were lower for uncinate process cancer. Locoregional recurrence was more frequent (p=0.017) and earlier (12 months vs. 36 months; p=0.002) in patients with uncinate process cancer than in patients with non-uncinate process pancreatic head cancer. In conclusion, uncinate process cancer is more likely to invade blood vessel and has worse prognosis due to the earlier and more frequent locoregional recurrence.